(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to explore the impact of fiqh-based views of Sheikh Mustafa Al-Zarqa on insurance contracts. It aims to identify the aspects of agreement and disagreement between the fiqh-based views of Sheikh Mustafa Al-Zarqa in this regard and other views. In terms of the fiqh-based views of Sheikh Mustafa Al-Zarqa in terms of insurance, the researchers found that the name of this Sheikh has been always linked with considering insurance halal. The latter Sheikh states – in his writings and Fatawi- that insurance is halal. He suggests that insurance of all type is halal. That applies to insurance on things, insurance against liability, and life insurance. In addition to claiming that insurance is halal, the latter Sheikh believes that insurance is Wajib (obligatory) in some cases in order to preserve lives, or properties (e.g. orphans’ properties). He sheds a light on the proofs provided by the ones who consider the business insurance contract haram. He sheds a light on the proofs provided by the ones who consider some types of insurance haram and other types of insurance halal. He confirms that the insurance contract is a form of compensation contract. He adds that such compensations aims at providing both of the contract parties with benefits. To illustrate more, the insurance company shall receive the installments paid by the insured people. As for the insured people, they shall enjoy a sense of security against risks. That is because the insured people shall get a compensation in case they suffered from any damage.